Differences in the Plastispheres of Biodegradable and Non-biodegradable Plastics: A Mini Review - Peng, Chu; Wang, Jiao; Liu, Xianhua; Wang, Lei (Frontiers in Microbiology, 2022)
There has been a steady rise in the production and disposal of biodegradable plastics. Unlike the microorganisms present in the biofilms on non-biodegradable plastic surfaces (the “plastisphere”), the plastisphere of biodegradable plastic has not been well-characterized. As the polymer structure of biodegradable plastic has a higher microbial affinity than that of non-biodegradable plastic, their plastispheres are assumed to be different. This review summarizes the reported differences in microbial communities on the surface of biodegradable and non-biodegradable plastics, discusses the driving forces behind these differences and discusses the potential environmental risks. Overall, the plastisphere biomass on the surface of non-biodegradable plastic was observed to be lower than that of biodegradable plastic. The community structure of microbes in both plastispheres was diverse, mainly due to the properties of the plastic surface, such as surface charge, hydrophilicity/hydrophobicity, roughness, and bioavailability of polymer components for microbes. Further research should focus on developing biodegradable plastic that degrade faster in the environment, revealing the mechanism of enrichment of ARGs and potential pathogens on plastics, and understanding the potential influence of plastispheres on the evolution and selection of plastic-degrading microbial potential.